E-063 Primary results from the predict (pre-hospital emergency LVO detection during initial care transport) study: a prospective, multi-center, non-inferiority comparison between the novel PREDICT composite 4-item scale and the rapid arterial occlusion evaluation (RACE) scale to detect large-vessel occlusion (LVO) strokes when administered by us-based ems personnel to suspected stroke patients at the initial pre-hospital encounter. (4th August 2020) - James, R; Cruz, A; Fortuny, E; Ugiliweneza, B; Wang, D; White, A; Khattar, N; Adams, S; Gallinore, B; Ding, D; Wolfe, S; Heck, D
Abstract : Introduction: Accurate identification of large vessel occlusion (LVO) strokes in the pre-hospital setting is imperative to reduce time to thrombectomy and improve outcomes. Prior to this study, RACE was the only stroke severity scale designed to detect LVO that had been prospectively validated with Emergency Medical Services (EMS). The goal of our non-inferiority study is to prospectively validate and compare the novel PREDICT-3 item scale, PASS scale, and a composite of these two scales: the PREDICT Composite 4-item (PREDICT-4) scale to the RACE scale in detecting LVO in the prehospital setting. Methods: Adult patients suspected of having a stroke by EMS and transported to a participating comprehensive stroke center had both PREDICT-4 and RACE scales administered prospectively and recorded in a secure web-based database. Admission NIHSS score and final diagnosis were also recorded. Cerebrovascular imaging studies (CTA, MRA or DSA) were reviewed by a blinded, independent neuroradiologist to determine LVO diagnosis. LVO was defined as occlusion of intracranial internal carotid artery (ICA), middle cerebral artery (MCA) M1 portion, or proximal aspect of single or multiple M2 branches of MCA, or basilar artery (BA). We used SAS and c-statistics to create receiver-operating characteristic (ROC) curves to determine the area under the curve (AUC) and optimal score cut point (CP) for each scale. We also calculated the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and overall accuracy for each optimal CP score. Results: 250 subjects were enrolled, 17 were excluded for lack of neurovascular imaging, 1 was excluded for incomplete stroke scale data, leaving 232 subjects who met inclusion criteria for analysis. 31 subjects had LVO and the prevalence of LVO was 13.4%. In table 1, we report the performance of each stroke severity scale at their respective optimal CP. In our study, the optimal CP for RACE was ≥6 while the original RACE study was ≥5. Conclusions: This large, US-based, prospective, pre-hospital, EMS-administered study showed greater AUC for RACE. However, all three scales were non-inferior in AUC with respect to RACE. These newer, simpler scales may have acceptable diagnostic ability for LVO and be more easily adopted by EMS. Disclosures: R. James: 1; C; Medtronic, Medtronic. A. Cruz: None. E. Fortuny: None. B. Ugiliweneza: None. D. Wang: None. A. White: None. N. Khattar: None. S. Adams: None. B. Gallinore: None. D. Ding: None. S. Wolfe: None. D. Heck: None.